Tuff aggregate anti-corrosion concrete and preparation method thereof

By using tuff aggregate to resist corrosion concrete technical means in concrete, the durable diseases caused by salt soil corrosion and salt-containing environmental water erosion are solved, and the effect of improving the self-repair ability and compressive strength of concrete is achieved, which is extended. The service life of concrete and reduce maintenance costs.

CN119430756APending Publication Date: 2025-02-14中电建路桥集团有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411498586.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-14
Patent Text Reader

Abstract

The invention discloses tuff aggregate anti-corrosion concrete and a preparation method thereof. The method comprises the following steps: taking 50-120 parts of natural tuff, an admixture, an anti-corrosion additive and 160-190 parts of water; preparing a part of the admixture into a nanoscale admixture, preparing a part of the steel fibers into nanoscale steel fibers, uniformly mixing 60-90 parts of water, 6-20 parts of cationic polyacrylamide and a part of the water reducing agent, then adding the nanoscale admixture, the nanoscale steel fibers and a part of the natural tuff, and uniformly mixing; the method comprises the following steps: firstly, mixing the residual water reducing agent with the residual water, then uniformly mixing 280-360 parts of cement, 700-800 parts of fine aggregate and 800-820 parts of coarse aggregate with the residual admixture, the residual natural tuff and the residual steel fiber to obtain a primary concrete mixture, then pouring the mixture of the residual water reducing agent and the residual water into the primary concrete mixture, and uniformly mixing; and uniformly mixing the two mixtures to obtain the tuff aggregate anti-corrosion concrete. The prepared concrete system is high in compressive strength, good in anti-cracking performance and excellent in overall performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete and relates to tuff aggregate corrosion-resistant concrete and a preparation method thereof. Background Art

[0002] my country is a vast country with abundant resources. Some areas of the country are distributed with a large amount of saline soil due to unique geological conditions and special climate. The salt is mainly sulfate and chloride. As a result, the concrete structures and buildings in the region suffer from severe corrosion of saline soil and erosion of saline environmental water, resulting in different degrees of concrete corrosion, cracking, spalling and steel corrosion and other durability diseases, making their actual lifespan far less than the designed service life. The resulting repairs, reinforcements and even demolition and reconstruction have brought a lot of direct and indirect economic losses. Therefore, providing a new type of tuff aggregate corrosion-resistant concrete is an urgent technical problem that needs to be solved. Summary of the invention

[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0004] Still another object of the present invention is to provide a tuff aggregate corrosion resistant concrete.

[0005] To this end, the technical solution provided by the present invention is: A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 50-120 parts of natural tuff, 280-360 parts of cement, 700-800 parts of fine aggregate, 800-820 parts of coarse aggregate, admixtures, anti-corrosion admixtures and 160-190 parts of water, wherein the admixtures include 30-40 parts of slag, 20-50 parts of fly ash, 20-40 parts of metakaolin, 30-50 parts of silica fume and 5-20 parts of zeolite, and the anti-corrosion admixtures include 50-60 parts of steel fiber, 6-20 parts of cationic polyacrylamide and 8-10 parts of water reducer.

[0006] Preferably, in the tuff aggregate corrosion-resistant concrete, 50% to 60% of the steel fibers are nano-grade steel fibers, and the remaining steel fibers have a length not exceeding 30 mm and a diameter not exceeding 0.3 mm.

[0007] Preferably, in the tuff aggregate anti-corrosion concrete, the natural tuff has a surface area of ​​400-500m 2 / kg of tuff ultrafine powder, and subjecting the ultrafine tuff powder to microwave treatment at a microwave power of 600-900W for 10-20 minutes, and then keeping the microwave-treated tuff ultrafine powder at a temperature of 350-400°C for 5-10 minutes.

[0008] Preferably, in the tuff aggregate anti-corrosion concrete, 1% of the admixture is taken to make nano-scale admixture, and the particle size of the remaining admixture is ≤5 mm.

[0009] Preferably, the tuff aggregate anti-corrosion concrete further comprises 5 to 10 parts of an air entraining agent, and the air entraining agent is an alkyl aromatic hydrocarbon sulfonic acid air entraining agent or a saponin air entraining agent.

[0010] Preferably, in the tuff aggregate anti-corrosion concrete, the water reducer is a polycarboxylate water reducer.

[0011] Preferably, in the tuff aggregate anti-corrosion concrete, the fine aggregate is medium sand with a fineness modulus of 2.2 to 2.8, and the coarse aggregate is continuously graded crushed stone with a particle size of 5 to 15 mm.

[0012] The method for preparing the tuff aggregate corrosion-resistant concrete comprises the following steps: Step 1: Take 50-120 parts of natural tuff, 160-190 parts of admixtures, anti-corrosion admixtures and water in parts by weight, wherein the admixtures include 30-40 parts of slag, 20-30 parts of fly ash, 20-30 parts of metakaolin, 30-40 parts of silica fume and 5-10 parts of zeolite, and the anti-corrosion admixtures include 50-60 parts of steel fiber, 6-20 parts of cationic polyacrylamide and 8-10 parts of water reducer; Step 2: Take part of the admixture to make a nano-admixture, take part of the steel fiber to make a nano-steel fiber, take 60-90 parts of water, 6-20 parts of cationic polyacrylamide and part of the water reducer and mix them, then add the nano-admixture, nano-steel fiber and part of the natural tuff and mix them; Step 3: firstly, mix the remaining water reducer with the remaining water, then take 280-360 parts of cement, 700-800 parts of fine aggregate, 800-820 parts of coarse aggregate and mix them with the remaining admixture, the remaining natural tuff and the remaining steel fiber to obtain a primary concrete mixture, and then pour the mixture of the remaining water reducer and the remaining water into the primary concrete mixture and mix them; Step 4: Mix the mixture obtained in step 2 and the mixture obtained in step 3 to obtain tuff aggregate corrosion-resistant concrete.

[0013] Preferably, in the preparation method, in step 3, 5 to 10 parts of an air entraining agent are added to the primary concrete mixture. The air entraining agent is an alkyl aromatic sulfonic acid air entraining agent or a saponin air entraining agent.

[0014] Preferably, in the preparation method, in step 2, the portion of water reducer accounts for 40% to 50% of the total amount of water reducer, the portion of steel fiber accounts for 50% to 60% of the total amount of steel fiber, the portion of admixture accounts for 1% of the total amount of admixture, and the portion of natural tuff accounts for 5% to 10% of the total amount of natural tuff.

[0015] Preferably, in the preparation method, the length of the remaining steel fibers does not exceed 30 mm and the diameter does not exceed 0.3 mm.

[0016] Preferably, in the preparation method, the natural tuff has a surface area of ​​400-500m 2 / kg of tuff ultrafine powder, and subjecting the ultrafine tuff powder to microwave treatment at a microwave power of 600-900W for 10-20 minutes, and then keeping the microwave-treated tuff ultrafine powder at a temperature of 350-400°C for 5-10 minutes.

[0017] Preferably, in the preparation method, the particle size of the remaining admixture is ≤5 mm.

[0018] Preferably, in the preparation method, the water reducer is a polycarboxylate water reducer.

[0019] Preferably, in the preparation method, the fine aggregate is medium sand with a fineness modulus of 2.2 to 2.8, and the coarse aggregate is continuously graded crushed stone with a particle size of 5 to 15 mm.

[0020] The present invention has at least the following beneficial effects: The tuff aggregate anti-corrosion concrete of the present invention is made by combining tuff powder and admixtures, wherein the admixtures include 30 to 40 parts of slag, 20 to 50 parts of fly ash, 20 to 40 parts of metakaolin, 30 to 50 parts of silica fume and 5 to 20 parts of zeolite. The fly ash, slag, metakaolin, silica fume and zeolite are used together to neutralize the alkaline components to a large extent and have chloride ion resistance, thereby improving the self-repairing effect of the concrete. At the same time, the expansion of the tuff powder is suppressed by adding cationic polyacrylamide, and the reactants thereof with tuff and steel fibers are evenly distributed in the concrete, so that the structure of the concrete is more compact, and its compressive strength and crack resistance are improved. 50% to 60% of the steel fibers are nano-scale steel fibers, and the length of the remaining steel fibers does not exceed 30 mm and the diameter does not exceed 0.3 mm. Nano-scale steel fibers can be distributed more evenly so as to better interact with other components. The natural tuff is made of a surface area of ​​400 to 500 m 2 / kg of tuff ultrafine powder, and the tuff ultrafine powder is subjected to microwave treatment at a microwave power of 600-900W for 10-20 minutes, and then the microwave-treated tuff ultrafine powder is kept at a temperature of 350-400°C for 5-10 minutes. The activity of the tuff ultrafine powder treated above is improved, and it can react with a large amount of strong calcium oxide generated in cement hydration to produce hydrated calcium aluminate gel and hydrated calcium silicate gel, thereby improving the mechanical properties of concrete.

[0021] In addition, when preparing the concrete of the present invention, part of the admixture is taken to make a nano-admixture, part of the steel fiber is taken to make a nano-steel fiber, part of the water, cationic polyacrylamide and part of the water reducer are mixed, and then the nano-admixture, nano-steel fiber and part of the natural tuff are added thereto and mixed, and part of the water, cationic polyacrylamide and part of the water reducer are mixed, which can give full play to the maximum performance of the cationic polyacrylamide, and when the nano-admixture, nano-steel fiber and natural tuff are fused, the contact surface can be increased, the alkaline components can be neutralized to the maximum extent, the expansion effect of the tuff powder can be suppressed, and the self-repairing effect of the concrete can be improved. The structure of the concrete is made denser, and its compressive strength and crack resistance are improved.

[0022] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0024] It should be understood that terms such as “having”, “including” and “comprising” used herein do not specify the existence or addition of one or more other elements or combinations thereof.

[0025] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0026] The present invention provides a tuff aggregate anti-corrosion concrete, which comprises the following components in parts by weight: 50-120 parts of natural tuff, 280-360 parts of cement, 700-800 parts of fine aggregate, 800-820 parts of coarse aggregate, admixtures, anti-corrosion admixtures and 160-190 parts of water, wherein the admixtures include 30-40 parts of slag, 20-50 parts of fly ash, 20-40 parts of metakaolin, 30-50 parts of silica fume and 5-20 parts of zeolite, and the anti-corrosion admixtures include 50-60 parts of steel fiber, 6-20 parts of cationic polyacrylamide and 8-10 parts of water reducer.

[0027] The tuff aggregate anti-corrosion concrete of the present invention cooperates with tuff powder and admixtures, and the admixtures include 30-40 parts of slag, 20-50 parts of fly ash, 20-40 parts of metakaolin, 30-50 parts of silica fume and 5-20 parts of zeolite. The fly ash, slag, metakaolin, silica fume and zeolite are used together to neutralize alkaline components to a large extent and have chloride ion resistance, thereby improving the self-repairing effect of concrete. At the same time, the expansion effect of tuff powder is suppressed by adding cationic polyacrylamide, and the reactants of tuff and steel fibers are evenly distributed in concrete, so that the structure of concrete is more compact, and its compressive strength and crack resistance are improved.

[0028] In one embodiment of the present invention, preferably, 50% to 60% of the steel fibers are nano-scale steel fibers, and the remaining steel fibers are no longer than 30 mm and no larger than 0.3 mm in diameter. Nano-scale steel fibers can be distributed more evenly to better interact with other components.

[0029] In one embodiment of the present invention, preferably, the natural tuff has a surface area of ​​400-500m 2 / kg of tuff ultrafine powder, and the tuff ultrafine powder is subjected to microwave treatment at a microwave power of 600-900W for 10-20 minutes, and then the microwave-treated tuff ultrafine powder is kept at a temperature of 350-400°C for 5-10 minutes. The activity of the tuff ultrafine powder treated above is improved, and it can react with a large amount of strong calcium oxide generated in cement hydration to produce hydrated calcium aluminate gel and hydrated calcium silicate gel, thereby improving the mechanical properties of concrete.

[0030] In one of the schemes of the present invention, preferably, 1% of the admixture is taken to make a nano-scale admixture, and the particle size of the remaining admixture is ≤5 mm.

[0031] In one of the schemes of the present invention, preferably, 5 to 10 parts of an air entraining agent are further included, and the air entraining agent is an alkyl aromatic sulfonic acid air entraining agent or a saponin air entraining agent.

[0032] In one embodiment of the present invention, preferably, the water reducer is a polycarboxylate water reducer.

[0033] In one of the schemes of the present invention, preferably, the fine aggregate is medium sand with a fineness modulus of 2.2-2.8, and the coarse aggregate is continuously graded crushed stone with a particle size of 5-15 mm.

[0034] The present invention also provides a method for preparing tuff aggregate corrosion-resistant concrete, comprising the following steps: Step 1: Take 50-120 parts of natural tuff, 160-190 parts of admixtures, anti-corrosion admixtures and water in parts by weight, wherein the admixtures include 30-40 parts of slag, 20-30 parts of fly ash, 20-30 parts of metakaolin, 30-40 parts of silica fume and 5-10 parts of zeolite, and the anti-corrosion admixtures include 50-60 parts of steel fiber, 6-20 parts of cationic polyacrylamide and 8-10 parts of water reducer; Step 2: Take part of the admixture to make a nano-admixture, take part of the steel fiber to make a nano-steel fiber, take 60-90 parts of water, 6-20 parts of cationic polyacrylamide and part of the water reducer and mix them, then add the nano-admixture, nano-steel fiber and part of the natural tuff and mix them; Step 3: firstly, mix the remaining water reducer with the remaining water, then take 280-360 parts of cement, 700-800 parts of fine aggregate, 800-820 parts of coarse aggregate and mix them with the remaining admixture, the remaining natural tuff and the remaining steel fiber to obtain a primary concrete mixture, and then pour the mixture of the remaining water reducer and the remaining water into the primary concrete mixture and mix them; Step 4: Mix the mixture obtained in step 2 and the mixture obtained in step 3 to obtain tuff aggregate corrosion-resistant concrete.

[0035] When preparing the concrete of the present invention, part of the admixture is taken to make a nano-admixture, part of the steel fiber is taken to make a nano-steel fiber, part of the water, cationic polyacrylamide and part of the water reducer are mixed, and then the nano-admixture, nano-steel fiber and part of the natural tuff are added thereto and mixed, and part of the water, cationic polyacrylamide and part of the water reducer are mixed to maximize the performance of the cationic polyacrylamide, and when the nano-admixture, nano-steel fiber and natural tuff are fused, the contact surface can be increased, the alkaline components can be neutralized to the maximum extent, and the self-repairing effect of the concrete can be improved. The expansion effect of the tuff powder is suppressed.

[0036] In one of the solutions of the present invention, preferably, in step three, 5 to 10 parts of air entraining agent are added to the primary concrete mixture.

[0037] In one of the schemes of the present invention, preferably, in step 2, the part of the water reducer accounts for 40% to 50% of the total amount of the water reducer, the part of the steel fiber accounts for 50% to 60% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 5% to 10% of the total amount of the natural tuff.

[0038] In one embodiment of the present invention, preferably, 5 to 10 parts of an air entraining agent are added to the primary concrete mixture. The air entraining agent is an alkyl aromatic sulfonic acid air entraining agent or a saponin air entraining agent.

[0039] In one of the schemes of the present invention, preferably, the part of the water reducer accounts for 40% to 50% of the total amount of the water reducer, the part of the steel fiber accounts for 50% to 60% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 5% to 10% of the total amount of the natural tuff.

[0040] In one embodiment of the present invention, preferably, the length of the remaining steel fibers does not exceed 30 mm and the diameter does not exceed 0.3 mm.

[0041] In one embodiment of the present invention, the natural tuff preferably has a surface area of ​​400 to 500 m 2 / kg of tuff ultrafine powder, and subjecting the ultrafine tuff powder to microwave treatment at a microwave power of 600-900W for 10-20 minutes, and then keeping the microwave-treated tuff ultrafine powder at a temperature of 350-400°C for 5-10 minutes.

[0042] In one embodiment of the present invention, preferably, the particle size of the remaining admixture is ≤5 mm.

[0043] In one embodiment of the present invention, preferably, the water reducer is a polycarboxylate water reducer.

[0044] In one solution of the present invention, preferably, the fine aggregate is medium sand with a fineness modulus of 2.2 to 2.8, and the coarse aggregate is continuously graded crushed stone with a particle size of 5 to 15 mm.

[0045] The following embodiments are provided to further illustrate the technical solution of the present invention: Example 1 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 50 parts of natural tuff, 280 parts of cement, 700 parts of fine aggregate, 800 parts of coarse aggregate, admixture, anti-corrosion admixture and 160 parts of water, wherein the admixture includes 30 parts of slag, 20 parts of fly ash, 20 parts of metakaolin, 30 parts of silica fume and 5 parts of zeolite, and the anti-corrosion admixture includes 50 parts of steel fiber, 6 parts of cationic polyacrylamide and 8 parts of water reducer. 50% to 60% of the steel fiber is nano-grade steel fiber, and the length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm. Take 1% of the admixture to make nano-grade admixture, and the particle size of the remaining admixture is ≤5 mm. The fine aggregate is medium sand with a fineness modulus of 2.2 to 2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5 to 15mm.

[0046] The method for preparing the above-mentioned tuff aggregate corrosion-resistant concrete comprises the following steps: 1) Use a ball mill to grind natural tuff into ultra-fine tuff powder with a surface area of ​​400~500m 2 / kg, and the tuff ultrafine powder was subjected to microwave treatment at a microwave power of 600 W for 10 minutes, and then the microwave-treated tuff ultrafine powder was kept at a temperature of 350° C. for 5 minutes.

[0047] 2) Take part of the admixture to make a nano-grade admixture, take part of the steel fiber to make a nano-grade steel fiber, take 60 parts of water, 6 parts of cationic polyacrylamide and part of the water reducer and mix them evenly, then add the nano-grade admixture, nano-grade steel fiber and part of the natural tuff thereto and mix them evenly, the part of the water reducer accounts for 40% of the total amount of the water reducer, the part of the steel fiber accounts for 50% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 5% of the total amount of the natural tuff.

[0048] 3) First, mix the remaining water reducer with the remaining water, then take all the cement, fine aggregate, coarse aggregate, air entraining agent and mix with the remaining admixtures, remaining natural tuff, and remaining steel fibers to obtain a primary concrete mixture, and then pour the mixture of the remaining water reducer and the remaining water into the primary concrete mixture and mix. The length of the remaining steel fiber does not exceed 30 mm and the diameter does not exceed 0.3 mm, and the particle size of the remaining admixture is ≤ 5 mm.

[0049] 4) The mixture obtained in step 2) and the mixture obtained in step 3) are mixed to obtain tuff aggregate anti-corrosion concrete.

[0050] Example 2 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 60 parts of natural tuff, 290 parts of cement, 720 parts of fine aggregate, 805 parts of coarse aggregate, admixture, anti-corrosion admixture, 5 parts of air entraining agent and 165 parts of water, wherein the admixture includes 32 parts of slag, 25 parts of fly ash, 25 parts of metakaolin, 32 parts of silica fume and 8 parts of zeolite, and the anti-corrosion admixture includes 52 parts of steel fiber, 8 parts of cationic polyacrylamide and 9 parts of polycarboxylic acid water reducer. 52% of the steel fiber is nano-grade steel fiber, and the length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm. 1% of the admixture is taken to make nano-grade admixture, and the particle size of the remaining admixture is ≤5 mm. The air entraining agent is an alkyl aromatic hydrocarbon sulfonic acid air entraining agent. The fine aggregate is medium sand with a fineness modulus of 2.2~2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5~15mm.

[0051] The method for preparing the above-mentioned tuff aggregate anti-corrosion concrete comprises the following steps: 1) Use a ball mill to grind natural tuff into ultra-fine tuff powder with a surface area of ​​400~500m 2 / kg, and the ultrafine tuff powder is subjected to microwave treatment at a microwave power of 650 W for 12 minutes, and then the ultrafine tuff powder after microwave treatment is kept at a temperature of 360°C for 6 minutes.

[0052] 2) Take part of the admixture to make a nano-grade admixture, take part of the steel fiber to make a nano-grade steel fiber, take 65 parts of water, 8 parts of cationic polyacrylamide and part of the polycarboxylate water reducer and mix them evenly, then add the nano-grade admixture, nano-grade steel fiber and part of the natural tuff thereto and mix them evenly, the part of the polycarboxylate water reducer accounts for 42% of the total amount of the polycarboxylate water reducer, the part of the steel fiber accounts for 52% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 6% of the total amount of the natural tuff.

[0053] 3) First, mix the remaining polycarboxylate water reducer with the remaining water, then take all the cement, fine aggregate, coarse aggregate, air entraining agent and mix with the remaining admixture, remaining natural tuff and remaining steel fiber to obtain a primary concrete mixture, and then pour the mixture of the remaining polycarboxylate water reducer and the remaining water into the primary concrete mixture and mix. The length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm, and the particle size of the remaining admixture is ≤5mm.

[0054] 4) The mixture obtained in step 2) and the mixture obtained in step 3) are mixed to obtain tuff aggregate anti-corrosion concrete.

[0055] Example 3 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 70 parts of natural tuff, 300 parts of cement, 740 parts of fine aggregate, 810 parts of coarse aggregate, admixture, anti-corrosion admixture, 6 parts of air entraining agent and 170 parts of water, wherein the admixture includes 34 parts of slag, 30 parts of fly ash, 30 parts of metakaolin, 34 parts of silica fume and 10 parts of zeolite, and the anti-corrosion admixture includes 54 parts of steel fiber, 10 parts of cationic polyacrylamide and 10 parts of polycarboxylic acid water reducer. 54% of the steel fiber is nano-grade steel fiber, and the length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm. 1% of the admixture is taken to make nano-grade admixture, and the particle size of the remaining admixture is ≤5 mm. The air entraining agent is a saponin air entraining agent. The fine aggregate is medium sand with a fineness modulus of 2.2~2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5~15mm.

[0056] The method for preparing the above-mentioned tuff aggregate corrosion-resistant concrete comprises the following steps: 1) Use a ball mill to grind natural tuff into ultra-fine tuff powder with a surface area of ​​400~500m 2 / kg, and the tuff ultrafine powder was subjected to microwave treatment at a microwave power of 700 W for 14 minutes, and then the microwave-treated tuff ultrafine powder was kept at a temperature of 370°C for 7 minutes.

[0057] 2) Take part of the admixture to make a nano-grade admixture, take part of the steel fiber to make a nano-grade steel fiber, take 70 parts of water, 10 parts of cationic polyacrylamide and part of the polycarboxylate water reducer and mix them evenly, then add the nano-grade admixture, nano-grade steel fiber and part of the natural tuff thereto and mix them evenly, the part of the polycarboxylate water reducer accounts for 44% of the total amount of the polycarboxylate water reducer, the part of the steel fiber accounts for 54% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 7% of the total amount of the natural tuff.

[0058] 3) First, the remaining polycarboxylate water reducer is mixed with the remaining water, and then all the cement, 700-800 parts of fine aggregate, coarse aggregate, air entraining agent are mixed with the remaining admixture, the remaining natural tuff, and the remaining steel fiber to obtain a primary concrete mixture, and then the mixture of the remaining polycarboxylate water reducer and the remaining water is poured into the primary concrete mixture and mixed; the air entraining agent is a saponin air entraining agent. The length of the remaining steel fiber does not exceed 30 mm and the diameter does not exceed 0.3 mm, and the particle size of the remaining admixture is ≤5 mm.

[0059] 4) The mixture obtained in step 2) and the mixture obtained in step 3) are mixed to obtain tuff aggregate anti-corrosion concrete.

[0060] Example 4 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 85 parts of natural tuff, 320 parts of cement, 750 parts of fine aggregate, 810 parts of coarse aggregate, admixture, anti-corrosion admixture, 7.5 parts of air entraining agent and 175 parts of water, wherein the admixture includes 35 parts of slag, 35 parts of fly ash, 30 parts of metakaolin, 40 parts of silica fume and 12.5 parts of zeolite, and the anti-corrosion admixture includes 55 parts of steel fiber, 13 parts of cationic polyacrylamide and 9 parts of polycarboxylic acid water reducer. 55% of the steel fiber is nano-grade steel fiber, and the length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm. 1% of the admixture is taken to make nano-grade admixture, and the particle size of the remaining admixture is ≤5 mm. The air entraining agent is an alkyl aromatic hydrocarbon sulfonic acid air entraining agent. The fine aggregate is medium sand with a fineness modulus of 2.2~2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5~15mm.

[0061] The method for preparing the above-mentioned tuff aggregate anti-corrosion concrete comprises the following steps: 1) Use a ball mill to grind natural tuff into ultra-fine tuff powder with a surface area of ​​400~500m 2 / kg, and the ultrafine tuff powder is subjected to microwave treatment at a microwave power of 750 W for 15 minutes, and then the ultrafine tuff powder after microwave treatment is kept at a temperature of 375°C for 7.5 minutes.

[0062] 2) Take part of the admixture to make a nano-grade admixture, take part of the steel fiber to make a nano-grade steel fiber, take 75 parts of water, 13 parts of cationic polyacrylamide and part of the polycarboxylate water reducer and mix them evenly, then add the nano-grade admixture, nano-grade steel fiber and part of the natural tuff thereto and mix them evenly, the part of the polycarboxylate water reducer accounts for 45% of the total amount of the polycarboxylate water reducer, the part of the steel fiber accounts for 55% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 7.5% of the total amount of the natural tuff.

[0063] 3) First, the remaining polycarboxylate water reducer is mixed with the remaining water, then all the cement, fine aggregate, coarse aggregate, and 7.5 parts of air entraining agent are taken and mixed with the remaining admixture, the remaining natural tuff, and the remaining steel fiber to obtain a primary concrete mixture, and then the mixture of the remaining polycarboxylate water reducer and the remaining water is poured into the primary concrete mixture and mixed; the air entraining agent is an alkyl aromatic sulfonic acid air entraining agent. The length of the remaining steel fiber does not exceed 30 mm and the diameter does not exceed 0.3 mm, and the particle size of the remaining admixture is ≤5 mm.

[0064] 4) The mixture obtained in step 2) and the mixture obtained in step 3) are mixed to obtain tuff aggregate anti-corrosion concrete.

[0065] Example 5 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 100 parts of natural tuff, 340 parts of cement, 780 parts of fine aggregate, 818 parts of coarse aggregate, admixture, anti-corrosion admixture, 8.5 parts of air entraining agent and 180 parts of water, wherein the admixture includes 38 parts of slag, 46 parts of fly ash, 38 parts of metakaolin, 46 parts of silica fume and 18 parts of zeolite, and the anti-corrosion admixture includes 58 parts of steel fiber, 18 parts of cationic polyacrylamide and 9 parts of polycarboxylic acid water reducer. 58% of the steel fiber is nano-grade steel fiber, and the length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm. 1% of the admixture is taken to make nano-grade admixture, and the particle size of the remaining admixture is ≤5 mm. The air entraining agent is a saponin air entraining agent. The fine aggregate is medium sand with a fineness modulus of 2.2~2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5~15mm.

[0066] The method for preparing the above-mentioned tuff aggregate anti-corrosion concrete comprises the following steps: 1) Use a ball mill to grind natural tuff into ultra-fine tuff powder with a surface area of ​​400~500m 2 / kg, and the ultrafine tuff powder was subjected to microwave treatment at a microwave power of 820 W for 18 minutes, and then the ultrafine tuff powder after microwave treatment was kept at a temperature of 380°C for 8 minutes.

[0067] 2) Take part of the admixture to make a nano-grade admixture, take part of the steel fiber to make a nano-grade steel fiber, take 85 parts of water, 18 parts of cationic polyacrylamide and part of the polycarboxylate water reducer and mix them evenly, then add the nano-grade admixture, nano-grade steel fiber and part of the natural tuff thereto and mix them evenly, the part of the polycarboxylate water reducer accounts for 48% of the total amount of the polycarboxylate water reducer, the part of the steel fiber accounts for 58% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 9% of the total amount of the natural tuff.

[0068] 3) First, the remaining polycarboxylate water reducer is mixed with the remaining water, and then all the cement, fine aggregate, coarse aggregate, and air entraining agent are taken and mixed with the remaining admixture, the remaining natural tuff, and the remaining steel fiber to obtain a primary concrete mixture, and then the mixture of the remaining polycarboxylate water reducer and the remaining water is poured into the primary concrete mixture and mixed; the air entraining agent is an alkyl aromatic sulfonic acid air entraining agent. The length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm, and the particle size of the remaining admixture is ≤5mm.

[0069] 4) The mixture obtained in step 2) and the mixture obtained in step 3) are mixed to obtain tuff aggregate anti-corrosion concrete.

[0070] Example 6 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 120 parts of natural tuff, 360 parts of cement, 800 parts of fine aggregate, 820 parts of coarse aggregate, admixture, anti-corrosion admixture and 190 parts of water, wherein the admixture includes 40 parts of slag, 50 parts of fly ash, 40 parts of metakaolin, 50 parts of silica fume and 20 parts of zeolite, and the anti-corrosion admixture includes 60 parts of steel fiber, 20 parts of cationic polyacrylamide and 10 parts of polycarboxylic acid water reducer. 60% of the steel fiber is nano-grade steel fiber, and the length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm. 1% of the admixture is taken to make nano-grade admixture, and the particle size of the remaining admixture is ≤5 mm. 10 parts of air entraining agent, the air entraining agent is an alkyl aromatic sulfonic acid air entraining agent or a saponin air entraining agent. The fine aggregate is medium sand with a fineness modulus of 2.2~2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5~15mm.

[0071] The method for preparing the above-mentioned tuff aggregate corrosion-resistant concrete comprises the following steps: 1) Use a ball mill to grind natural tuff into ultra-fine tuff powder with a surface area of ​​400~500m 2 / kg, and the ultrafine tuff powder is subjected to microwave treatment at a microwave power of 900 W for 20 minutes, and then the ultrafine tuff powder after microwave treatment is kept at a temperature of 400°C for 10 minutes.

[0072] 2) Take part of the admixture to make a nano-grade admixture, take part of the steel fiber to make a nano-grade steel fiber, take 90 parts of water, 20 parts of cationic polyacrylamide and part of the polycarboxylate water reducer and mix them evenly, then add the nano-grade admixture, nano-grade steel fiber and part of the natural tuff thereto and mix them evenly, the part of the polycarboxylate water reducer accounts for 50% of the total amount of the polycarboxylate water reducer, the part of the steel fiber accounts for 60% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 10% of the total amount of the natural tuff.

[0073] 3) First, the remaining polycarboxylate water reducer is mixed with the remaining water, and then all the cement, fine aggregate, coarse aggregate, air entraining agent are taken and mixed with the remaining admixture, the remaining natural tuff, and the remaining steel fiber to obtain a primary concrete mixture, and then the mixture of the remaining polycarboxylate water reducer and the remaining water is poured into the primary concrete mixture and mixed; the air entraining agent is an alkyl aromatic sulfonic acid air entraining agent or a saponin air entraining agent. The length of the remaining steel fiber does not exceed 30 mm and the diameter does not exceed 0.3 mm, and the particle size of the remaining admixture is ≤5 mm.

[0074] 4) The mixture obtained in step 2) and the mixture obtained in step 3) are mixed to obtain tuff aggregate anti-corrosion concrete.

[0075] Comparative Example 1 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 85 parts of natural tuff, 320 parts of cement, 750 parts of fine aggregate, 810 parts of coarse aggregate, anti-corrosion admixture, 7.5 parts of air entraining agent and 175 parts of water, wherein the anti-corrosion admixture includes 55 parts of steel fiber, 13 parts of cationic polyacrylamide and 9 parts of polycarboxylic acid water reducer. The air entraining agent is an alkyl aromatic hydrocarbon sulfonic acid air entraining agent. The fine aggregate is medium sand with a fineness modulus of 2.2 to 2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5 to 15 mm.

[0076] The method for preparing the above-mentioned tuff aggregate corrosion-resistant concrete comprises the following steps: 1) Mix 85 parts of natural tuff, 320 parts of cement, 750 parts of fine aggregate, 810 parts of coarse aggregate and 7.5 parts of air entraining agent; 2) Mix the anti-corrosion admixture including 55 parts of steel fiber, 13 parts of cationic polyacrylamide, 9 parts of polycarboxylate water reducer and 175 parts of water; 3) The mixture obtained in step 2) and the mixture obtained in step 1) are mixed evenly to obtain tuff aggregate anti-corrosion concrete.

[0077] Comparative Example 2 A tuff aggregate anti-corrosion concrete, comprising the following components in parts by weight: 85 parts of natural tuff, 320 parts of cement, 750 parts of fine aggregate, 810 parts of coarse aggregate, anti-corrosion admixture, 7.5 parts of air entraining agent and 175 parts of water, wherein the anti-corrosion admixture includes 55 parts of steel fiber, 13 parts of cationic polyacrylamide and 9 parts of polycarboxylic acid water reducer. 55% of the steel fiber is nano-grade steel fiber, and the length of the remaining steel fiber does not exceed 30mm and the diameter does not exceed 0.3mm. The air entraining agent is an alkyl aromatic hydrocarbon sulfonic acid air entraining agent. The fine aggregate is medium sand with a fineness modulus of 2.2~2.8, and the coarse aggregate is a continuously graded crushed stone with a particle size of 5~15mm.

[0078] The method for preparing the above-mentioned tuff aggregate corrosion-resistant concrete comprises the following steps: 1) Mix 60-90 parts of water, 6-20 parts of cationic polyacrylamide and part of water reducer, then add nano steel fiber and part of natural tuff and mix well; 2) First, the remaining water reducer is mixed with the remaining water, and then cement, fine aggregate, coarse aggregate, air entraining agent are mixed with the remaining admixtures, the remaining natural tuff, and the remaining steel fiber to obtain a primary concrete mixture, and then the mixture of the remaining water reducer and the remaining water is poured into the primary concrete mixture and mixed; 3) The mixture obtained in step 2) and the mixture obtained in step 3) are mixed to obtain tuff aggregate anti-corrosion concrete.

[0079] Table 1 shows the performance indicators of the concrete prepared in Examples 1 to 6 and Comparative Examples 1 and 2. The mechanical property test refers to the test method in GB·T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".

[0080] Table 1 Concrete performance test results project 28-day compressive strength (Mpa) Initial cracking time (minutes) Example 1 62.5 87 Example 2 63.1 88.5 Example 3 60.8 90 Example 4 66.7 95 Example 5 65.2 91 Example 6 63.3 90 Comparative Example 1 40.3 43 Comparative Example 2 45.0 50 It can be seen from Table 1 that the concrete system prepared by the present invention has high compressive strength, good crack resistance and excellent overall performance.

[0081] The number of modules and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention are obvious to those skilled in the art.

[0082] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A tuff aggregate anti-corrosion concrete, characterized in that: In parts by weight, it includes the following components: 50-120 parts of natural tuff, 280-360 parts of cement, 700-800 parts of fine aggregate, 800-820 parts of coarse aggregate, admixtures, anti-corrosion admixtures and 160-190 parts of water, wherein the admixtures include 30-40 parts of slag, 20-50 parts of fly ash, 20-40 parts of metakaolin, 30-50 parts of silica fume and 5-20 parts of zeolite, and the anti-corrosion admixtures include 50-60 parts of steel fiber, 6-20 parts of cationic polyacrylamide and 8-10 parts of water reducer.

2. The tuff aggregate anti-corrosion concrete according to claim 1, characterized in that: 50% to 60% of the steel fibers are nano-grade steel fibers, and the remaining steel fibers are no longer than 30 mm and no larger in diameter than 0.3 mm.

3. The tuff aggregate anti-corrosion concrete according to claim 1, characterized in that: The natural tuff has a surface area of ​​400-500m 2 / kg of tuff ultrafine powder, and subjecting the ultrafine tuff powder to microwave treatment at a microwave power of 600-900W for 10-20 minutes, and then keeping the microwave-treated tuff ultrafine powder at a temperature of 350-400°C for 5-10 minutes.

4. The tuff aggregate anti-corrosion concrete according to claim 1, characterized in that: 1% of the admixture is taken to prepare nano-scale admixture, and the particle size of the remaining admixture is ≤5 mm.

5. The tuff aggregate anti-corrosion concrete according to claim 1, characterized in that: The invention also comprises 5 to 10 parts of an air entraining agent, wherein the air entraining agent is an alkyl aromatic sulfonic acid air entraining agent or a saponin air entraining agent.

6. The tuff aggregate anti-corrosion concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

7. The tuff aggregate anti-corrosion concrete according to claim 1, characterized in that: The fine aggregate is medium sand with a fineness modulus of 2.2-2.8, and the coarse aggregate is continuously graded crushed stone with a particle size of 5-15 mm.

8. The method for preparing tuff aggregate anti-corrosion concrete according to claim 1, characterized in that: The steps include: Step 1: Take 50-120 parts of natural tuff, 160-190 parts of admixtures, anti-corrosion admixtures and water in parts by weight, wherein the admixtures include 30-40 parts of slag, 20-30 parts of fly ash, 20-30 parts of metakaolin, 30-40 parts of silica fume and 5-10 parts of zeolite, and the anti-corrosion admixtures include 50-60 parts of steel fiber, 6-20 parts of cationic polyacrylamide and 8-10 parts of water reducer; Step 2: Take part of the admixture to make a nano-admixture, take part of the steel fiber to make a nano-steel fiber, take 60-90 parts of water, 6-20 parts of cationic polyacrylamide and part of the water reducer and mix them, then add the nano-admixture, nano-steel fiber and part of the natural tuff and mix them; Step 3: firstly, mix the remaining water reducer with the remaining water, then take 280-360 parts of cement, 700-800 parts of fine aggregate, 800-820 parts of coarse aggregate and mix them with the remaining admixture, the remaining natural tuff and the remaining steel fiber to obtain a primary concrete mixture, and then pour the mixture of the remaining water reducer and the remaining water into the primary concrete mixture and mix them; Step 4: Mix the mixture obtained in step 2 and the mixture obtained in step 3 to obtain tuff aggregate corrosion-resistant concrete.

9. The preparation method according to claim 8, characterized in that: In step 3, 5 to 10 parts of air entraining agent are added to the primary concrete mixture.

10. The preparation method according to claim 8, characterized in that: In step 2, the part of the water reducer accounts for 40% to 50% of the total amount of the water reducer, the part of the steel fiber accounts for 50% to 60% of the total amount of the steel fiber, the part of the admixture accounts for 1% of the total amount of the admixture, and the part of the natural tuff accounts for 5% to 10% of the total amount of the natural tuff.